Rapid determination of trans-resveratrol in vegetable oils using magnetic hydrophilic multi-walled carbon nanotubes as adsorbents followed by liquid chromatography–tandem mass spectrometry. (1st July 2015) - Ma, Fei; Li, Peiwu; Zhang, Qi; Yu, Li; Zhang, Liangxiao
Highlights: Magnetic hydrophilic multiwalled carbon nanotubes were successfully prepared. The extraction procedure can be achieved in 10 min without tedious steps. Magnetic absorbents were applied to extract trans -resveratrol from oil samples. The method is simple and sensitive to analyze trans -resveratrol in lipid matrix. Abstract: In the present work, a rapid and simple procedure was developed and validated for the analysis of trans -resveratrol in vegetable oils based on magnetic hydrophilic multi-walled carbon nanotubes (h-MWCNT-MNPs) combined with liquid chromatography–tandem mass spectrometry (LC–MS/MS). h-MWCNT-MNPs were simply obtained by wrapping amine-functionalized Fe3 O4 magnetic nanoparticles into previously oxidized hydrophilic multi-walled carbon nanotubes. The major parameters affecting extraction efficiency were investigated, including the type and volume of desorption solvents, extraction and desorption time, washing solution, and sorbent amount. The limit of detection (LOD) and the limit of quantification (LOQ) were calculated as 0.6 and 2.0 μg/kg, respectively. The recoveries of trans- resveratrol in oil samples were in the range of 90.0–110.0% with RSDs of less than 17.5%. The results showed that only peanut oil contained trans- resveratrol, ranging from 8 ± 1 to 103 ± 12 μg/kg. The proposed method is reliable and robust, having an excellent potential for the analysis of trans -resveratrol in edible oils.